Tune in to rural radio - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
workshop was held in Ouagadougou (Burkina Faso) from 26-29 September 1995 to evaluate CTA's programme of activities for rural radio in ACP countries